2010
DOI: 10.1186/1471-2318-10-45
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy and the risk for community-acquired pneumonia

Abstract: BackgroundSome forms of pharmacotherapy are shown to increase the risk of community-acquired pneumonia (CAP). The purpose of this study is to investigate whether pharmacotherapy with proton pump inhibitors (PPI), inhaled corticosteroids, and atypical antipsychotics was associated with the increased risk for CAP in hospitalized older adults with the adjustment of known risk factors (such as smoking status and serum albumin levels).MethodsA retrospective case-control study of adults aged 65 years or older at a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
86
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(98 citation statements)
references
References 30 publications
(44 reference statements)
4
86
0
5
Order By: Relevance
“…Patients with COPD are at an increased risk of pneumonia 44,45 and the risks may be further increased by the use of ICS. 24,46 In a large case-control study, current ICS use was associated with a 70% increase in the rate of hospitalisation for pneumonia.…”
Section: Pneumoniamentioning
confidence: 99%
“…Patients with COPD are at an increased risk of pneumonia 44,45 and the risks may be further increased by the use of ICS. 24,46 In a large case-control study, current ICS use was associated with a 70% increase in the rate of hospitalisation for pneumonia.…”
Section: Pneumoniamentioning
confidence: 99%
“…Results have been conflicting, however, and a meta-analysis failed to draw a definite conclusion due to significant heterogeneity [1][2][3][4][5][6][7][8][9][10]. Some researchers are sceptical about the reported association because causality seemed improbable and results are suspected to be biased [11][12][13].…”
mentioning
confidence: 99%
“…Similarly, a differential risk of pneumonia associated with antipsychotic class was also observed by Barnett et al using a retrospective cohort study design [8]. Others studies found no differential risk or provided insufficient information [9,10].…”
mentioning
confidence: 74%
“…Three studies demonstrated that the risk of pneumonia varies by antipsychotic class, with a higher risk being attributed to atypical antipsychotics [4,[6][7][8][9]. A more recent finding is the demonstration of a differential risk associated with individual antipsychotic drugs [5,7].…”
Section: Expert Opinionmentioning
confidence: 99%